Interference Mitigation witb Adaptive Beamforming in Airport Gate Link - Haoyu Xu; Han Zhou; Liangyou Wang; Sunzeng Cai; Zhenghang Zhu (Dianxin kexue)
On the current most advanced commercial airplanes, IEEE 802.11b／g based system-terminal wireless LAN（TWLN）-is a wireless solution that is able to support the high speed wireless transmission for gate link. However, IEEE 802.11b／g has no resistibility against interference; due to the strong co-channel interference at the airport, the current gate link system provides a very low data rate. An IEEE 802.11g based adaptive beamforming method was provided that improved the performance of the current TWLN system. The simulation shows the proposed method is able to reject interference and significantly improve the system performance.